Renin inhibitor in hypertension treatment: from pharmacological point of view (Medical Journal of Indonesia, 2011)
The use of drugs that inhibit the renin-angiotensin system is one of the effective way to intervene in the pathogenesis of cardiovascular and renal disorders, especially in hypertension treatment. The idea of blocking the renin system at its origin by renin inhibitor has existed for more than 30 years. Renin inhibitor supresses the covension of angiotensinogen into angiotensin, and further deacreases the generation of the active peptide angiotensin II. The first generation (enalkiren) and second generation (remikiren) of orally active renin inhibitors were never used clinically because of low bioavailability and weak blood pressure-lowering activity. At present, aliskiren is the first non-peptide orally active renin inhibitor of the third generation to progress to phase III clinical trials and was approved by U.S. Food and Drug Administration (FDA) in March 2007. Aliskiren becomes the first renin inhibitor with indications for the treatment of hypertension in Indonesia, a compounds with improved oral bioavailability, specificity and efficacy. This review summarises the development of oral renin inhibitors, pharmacological aspects, with a focus on aliskiren. (Med J Indones 2011; 20:232-7)